Transformation of Organizational Cultural Values And Performance of Millennial Generation Lecturers of The University of North Sumatra - Arif Qaedi Hutagalung; Amlys Syahputra Silalahi; Doli Muhammad Ja’far Dalimunthe; Adika Fajar Putra (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This research aims to test the effect of the transformation of organizational cultural values on the performance of millennial lecturers. The data analysis techniques used are multiple linear analysis and descriptive statistical analysis. The determination of the sample was done by slovin margins of error method of error amounting to 10% of the total number of permanent lecturers of civil servants / non civil servants as many as 249 people and produced a sample of 71 people. Cultural transformation is measured by the dimensions of vision and mission; External environment; Willingness to achieve goals; Organizational image; Lecturer's needs and objectives; Interpersonal relationships; and Leadership. The results showed that the transformation of organizational cultural values at the University of North Sumatra had a positive barbarslot influence on the performance of millennial lecturers. These results show that the better implementation of the transformation of the cultural values of the University of North Sumatra will lead to improved performance of millennial lecturers. This research is expected to be used as input for the University to be able to pay attention and fulfill and fully support the needs of millennial lecturers of the University of North Sumatra to improve the performance of lecturers.